A CROSS-SECTIONAL COMPARISON OF SERUM HORMONE (FSH, TSH, GH) CONCENTRATIONS IN UNTREATED PATIENTS WITH PSYCHIATRIC DISORDER - Ambad, Ranjit S.; Jha, Roshan Kumar; Bankar, Nandkishor; Singh, Brij Raj; Ghogare, Ajinkya S.; Patil, Ragini (International Journal of Psychosocial Rehabilitation, 2020)
Mental health is being renowned as one of the primacy areas in health policies around the world and has also been comprised in the Sustainable Development Goals. Psychiatric disorder is categorised as panic disorder, generalised anxiety disorder, social anxiety disorder and many other types and sub types. Panic attacks are well-defined by the Diagnostic and Statistical Manual of Mental Health Disorders (DSM) as “an abrupt surge of intense fear or discomfort” reaching a peak in minutes. And anxiety disorder is the related with extreme fear, nervousness, apprehension, and associated behavioural disorders. Social anxiety disorder (SAD), (also known as social phobia), includes fear and anxiety about the social interaction and often related with avoidant behaviour.Case-control study with 2 groups of subjects, were taken followed by inclusion and exclusion criteria for characterisation. The study was approved by ethical board of DMIMSU. Hormones and their relationship with psychiatric disorder were estimated using different method. The levels of TSH were increased significantly (P < 0.001) in cases as compared to control group. There was significant change in levels of GH when cases were compared to control & also found to decrease significantly (P < 0.001) in cases as compared to control. However, the levels of FSH between cases and control was p=0. 001.Thus, for proper treatment of psychiatric disorders, information of the endocrine system and hormones effect on psychiatric disorder is precious. Patients with psychiatric disorder have higher levels of TSH and low level of GH. Our finding on hormones may provide new insight into a potentially modifiable way to diagnose psychiatric disorders